Analisis Resiko Fuel System Terhadap Kasus Low Power Engine Performance pada Unit Asphalt Finisher di PT. PP Presisi - Widada, Reza Ananda; Prihadianto, Braam Delfian; Wibowo, Setyawan Bekti; Harjono, Harjono (Department of Mechanical Engineering, Vocational College, Gadjah Mada University., 2024)
The fuel system plays an important role in the BOMAG BF 800 C Asphalt Finisher unit operating in road paving work. The engine performance of the BOMAG BF 800 C Asphalt Finisher unit will decrease if no fuel system is checked immediately. The purpose of this study is to analyze the fuel system that causes low power engine performance in the BOMAG BF 800 C Asphalt Finisher unit. The method used to solve these problems is a qualitative method using Fault Tree Analysis (FTA) analysis and Failure Mode and Effect Analysis (FMEA) as well as quantitative methods by calculating the mean time to failure (MTTF) and mean time to repair (MTTR) in accordance with the track record of using and repairing the BOMAG BF 800 C Asphalt Finisher unit. Based on the results of research that has been done, it is stated that the RPN value of the fuel injector is 324 and the fuel filter is 168. This calculation makes these components the most critical components in the case of low power engine performance. The specified maintenance activity interval on the fuel injector is 84 hours and the fuel filter is 35 hours.